A functional polymorphism in the SPINK5 gene is associated with asthma in a Chinese Han Population - Li Huaichen; Wang Pin; Li Jisheng; Zhang Wenjing; Xia Yu; Liu Qiji; Wei Chunhua; Gong Yaoqin (BMC, 2009)
Abstract Background Mutation in SPINK5 causes Netherton syndrome, a rare recessive skin disease that is accompanied by severe atopic manifestations including atopic dermatitis, allergic rhinitis, asthma, high serum IgE and hypereosinophilia. Recently, single nucleotide polymorphism (SNP) of the SPINK5 was shown to be significantly associated with atopy, atopic dermatitis, asthma, and total serum IgE. In order to determine the role of the SPINK5 in the development of asthma, a case-control study including 669 asthma patients and 711 healthy controls in Han Chinese was conducted. Methods Using PCR-RFLP assay, we genotyped one promoter SNP, -206G>A, and four nonsynonymous SNPs, 1103A>G (Asn368Ser), 1156G>A (Asp386Asn), 1258G>A (Glu420Lys), and 2475G>T (Glu825Asp). Also, we analyzed the functional significance of -206G>A using the luciferase reporter assay and electrophoresis mobility shift assay. Results we found that the G allele at SNP -206G>A was associated with increased asthma susceptibility in our study population (p = 0.002, odds ratio 1.34, 95% confidence interval 1.11-1.60). There was no significant association between any of four nonsynonymous SNPs and asthma. The A allele at -206G>A has a significantly higher transcriptional activity than the G allele. Electrophoresis mobility shift assay also showed a significantly higher binding efficiency of nuclear protein to the A allele compared with the G allele. Conclusion Our findings indicate that the -206G>A polymorphism in the SPINK5 is associated with asthma susceptibility in a Chinese Han population.